2020
DOI: 10.3389/fgene.2020.557846
|View full text |Cite
|
Sign up to set email alerts
|

Parental Effects on Epigenetic Programming in Gametes and Embryos of Dairy Cows

Abstract: The bovine represents an important agriculture species and dairy breeds have experienced intense genetic selection over the last decades. The selection of breeders focused initially on milk production, but now includes feed efficiency, health, and fertility, although these traits show lower heritability. The non-genetic paternal and maternal effects on the next generation represent a new research topic that is part of epigenetics. The evidence for embryo programming from both parents is increasing. Both oocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 158 publications
0
11
1
2
Order By: Relevance
“…Another example is provided by the epigenetic alterations that have been observed in semen collected at a peripubertal age. Embryos produced using such peripubertal semen display subtle modifications to the DNA methylome and transcriptome that particularly affect the genes involved in metabolic functions and protein synthesis ( Wu and Sirard, 2020 ). It is noteworthy that only morphologically normal embryos, which would likely have implanted and given birth to progeny, were considered during this study.…”
Section: Potential Mechanisms For the Programming Of Phenotypes Via The Paternal Routementioning
confidence: 99%
See 1 more Smart Citation
“…Another example is provided by the epigenetic alterations that have been observed in semen collected at a peripubertal age. Embryos produced using such peripubertal semen display subtle modifications to the DNA methylome and transcriptome that particularly affect the genes involved in metabolic functions and protein synthesis ( Wu and Sirard, 2020 ). It is noteworthy that only morphologically normal embryos, which would likely have implanted and given birth to progeny, were considered during this study.…”
Section: Potential Mechanisms For the Programming Of Phenotypes Via The Paternal Routementioning
confidence: 99%
“…The selection of AI bulls relies on their genetic merit, and they are usually obtained from the breeding of high breeding value sires and high-producing dairy cows. These cows are more likely to experience a negative energy balance in the event of concurrent lactation and gestation, which may lead to an unfavorable in utero environment for the developing fetus ( Wu and Sirard, 2020 ). Otherwise, practices to reduce the generation interval and accelerate genetic gain, such as hormonal treatments of the mothers, embryo technologies, or the hastened growth and puberty of male calves, may have a long-term impact on the sperm epigenome ( Rivera, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental factors may induce inheritable phenotypes in a nongenetic way in dairy cattle ( Wu & Sirard, 2020 ). A study published by our team showed that specific DNA methylation changes in sperm DNA were associated with bull age (early-, peri- and post-puberty) ( Lambert et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…A study published by our team showed that specific DNA methylation changes in sperm DNA were associated with bull age (early-, peri- and post-puberty) ( Lambert et al, 2018 ). A subsequent study showed that the age of the bull correlated with DNA methylation and transcriptome alterations in blastocysts, indicating a potential effect of age on offspring development ( Wu et al, 2020 ). Additionally, metabolic stress in cows resulted in alterations of the DNA methylation profile of embryos.…”
Section: Introductionmentioning
confidence: 99%
“…Э п и г е н е т и ч е с к и й а с п е к т в ы ж и в а е м о с т и э м б р и о н а. В живых организмах широко распространена эпигенетическая регуляция активности генов, которая не связана с изменением первичной структуры ДНК, но модифицирует работу генома в зависимости от внутренних и внешних факторов (110). Показано, что эпигенетическая регуляция осуществляется через химическую модификацию структуры ДНК (метилирование ДНК, модификации гистонов, некодирующие RNAs) или хроматина (111). Метилирование ДНК в бластоцистах -обратимый и динамический эпигенетический механизм, участвующий в ремоделировании структуры хроматина, в том числе в критических регуляторных областях генома, и тем самым влияющий на экспрессию генов (112).…”
unclassified